Comparison of Emission Spectrum in Series and Parallel Configured Dielectric Barrier Discharge (DBD) Reactors and Its Application for Textile Wastewater Treatment - Ahmad Faruq Abdurrahman; Kusumandari Kusumandari; Teguh Endah Saraswati (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Textile wastewater represents one of the world's largest aquatic pollutants due to industrial activities. Ozonation, an advanced oxidation process (AOP), serves as a cost-effective wastewater treatment method. This study compares emission spectra from series and parallel-configured dielectric barrier discharge (DBD) reactors and correlates them with ozone production for textile wastewater treatment. The discharge emission spectrum (OES) was analyzed to identify reactive species, while ozone concentration was quantified via titration. Ozonation was applied for 0–60 minutes, monitoring absorbance, dissolved oxygen (DO), total dissolved solids (TDS), total suspended solids (TSS), and conductivity. OES analysis revealed higher emission intensities of OH radicals and N₂ in the series configuration versus parallel, indicating enhanced plasma reactivity. Consequently, the series configuration yielded superior ozone production, achieving 53.14% degradation efficiency after 60 minutes. Significant reductions in absorbance, TDS, TSS, and conductivity occurred alongside increased DO. Longer treatment durations improved degradation efficiency.